Clinical resolution of periodontitis among diabetic patients under medical-dental coordinated care: A preliminary study in Kuantan - Yaacob, Munirah; Han, Tin Myo; Ismail, Razida; Sidek, Sorayah; Hari, Padmini; Aris, Mohd Aznan Md; Osman, Iskandar Firzada; Thuraiappah, Mahendran; Abdulla, Fa'iza; Sein, Than Tun; Saub, Roslan (University of Dicle, 2020)
The literature had reported the clinical resolution of periodontitis (CRP) in type-2 diabetic patients (T2DM-P) following non-surgical periodontal treatment (NSPT). However, the changes in glycemic control status during NSPT have not been presented clearly. Hence, this study was aimed to evaluate the CRP of T2DM-P under medical-and dental-coordinated care (M-DCC). A 6-month follow-up quasi-experimental study was conducted on 20 T2DM-P patients who underwent M-DCC in Kuantan. M-DCC, which included the standard diabetic care was administered by medical professionals at three health clinics, while NSPT by two periodontal specialists at their respective clinics. The target glycemic control achievement (TGCA), HbA1c. 6.5%. was assessed at 0 and 6 months post-NSPT. Clinical resolution of PD was measured in terms of the following parameters: (1) full mouth bleeding score (FMBS); (2) clinical attachment level (CAL) (mm); (3) probing pocket depth (PPD) (mm); as well as (4) PPDs of < 4 mm,. 4 mm, and. 6 mm at 0, 3, and 6 months post-NSPT respectively. Paired simple t-tests and ANOVA šgFšh tests were performed to interpret the clinical resolution of periodontitis as well as its relationship with TGCA. Of fifteen (25%) uncontrolled T2DM-P patients, two (10%) patients achieved the TGCA (HbA1c. 6.5%) at 6 months after the completion of NSPT and M-DCC. However, no significant reductions in the overall mean HbA1c values were noted. In spite of that, there were significant differences in the CRP and all periodontal parameters at baseline and 6-month follow-up. Nevertheless, there were no significant changes in the mean CAL (p > 0.05). NSPT, under M-DCC, gave rise to significant changes in the periodontal health of diabetic patients 6 months post-treatment. The effects of NSPT on HbA1c level were inconclusive. (WC:251). © 2019 University of Dicle.